ANALISIS PENDIDIKAN ISLAM DALAM KAJIAN AKHLAK DAN FIQIH - Riska Damayanti; Suci Lestari; Irda; Umi Nur Kholifatun (Program Studi Pendidikan Teknologi Informasi Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2024)
In the world of Islamic education, morality and fiqh are two important pillars that shape the personality and social life of a Muslim. Understanding of normative fiqh is sometimes perceived as rigid or less in accordance with the ever-changing social dynamics. Therefore, it is important to conduct an in-depth analysis of morality and fiqh material so that the material taught is not only theoretical, but also contextual and applicable. This analysis is expected to provide an overview of how morality and fiqh material can be taught more electively, and how to connect the two materials in forming a ballistic Muslim character. This study discusses the concept of morality in Islam with a focus on the perspective of fiqh. The purpose of this study is to analyze the relationship between morality and fiqh in the Qur'an and Hadith. The research method uses content analysis and literature study. The results of the study show that morality has an important role in shaping Muslim behavior. Conclusion, morality and fiqh have a close connection in Islam.